2022
DOI: 10.1021/acs.biochem.2c00210
|View full text |Cite
|
Sign up to set email alerts
|

Principles Governing the Phase Separation of Multidomain Proteins

Abstract: A variety of membraneless organelles, often termed “biological condensates”, play an important role in the regulation of cellular processes such as gene transcription, translation, and protein quality control. On the basis of experimental and theoretical investigations, liquid–liquid phase separation (LLPS) has been proposed as a possible mechanism for the origin of biological condensates. LLPS requires multivalent macromolecules that template the formation of long-range, intermolecular interaction networks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 143 publications
0
40
0
Order By: Relevance
“…In the scaffold-client model, liquid phase separation occurs through the formation of dense networks of intermolecular interactions, in which the multivalency of each constituent is provided by folded domains and/or by IDDs (P. Li et al., 2012 ; Shin and Brangwynne, 2017 ; Kamagata et al., 2021 ; Mohanty et al., 2022 ; Feng et al., 2021 ). Interactions between folded domains are specific and stoichiometrically defined.…”
Section: Promising Trends In Biomolecular Condensationmentioning
confidence: 99%
See 2 more Smart Citations
“…In the scaffold-client model, liquid phase separation occurs through the formation of dense networks of intermolecular interactions, in which the multivalency of each constituent is provided by folded domains and/or by IDDs (P. Li et al., 2012 ; Shin and Brangwynne, 2017 ; Kamagata et al., 2021 ; Mohanty et al., 2022 ; Feng et al., 2021 ). Interactions between folded domains are specific and stoichiometrically defined.…”
Section: Promising Trends In Biomolecular Condensationmentioning
confidence: 99%
“…However, the modern concept of domain as the unit of protein structure reconciles order, disorder and biological function. In fact, if one defines IDRs as rightly domains and thinks of multidomain proteins as composed of coexisting folded and intrinsically disordered domains (IDDs), a general function for the latter is envisaged: to allow multiple, long-range, and fuzzy interactions with different ligands and partners in large biological complexes ( Tompa and Fuxreiter, 2008 ); Uversky and Dunker (2010) ; Van Der Lee et al., 2014 ; Uversky and Finkelstein (2019) ; Mohanty et al. (2022) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrinsically disordered proteins (IDPs) or regions (IDRs) are a driving force in the formation of membraneless organelles that are responsible for many physiological functions, e.g., signaling, stress response, transcription, and metabolic processes. Due to the lack of well-defined three-dimensional folded structures, IDPs display remarkable heterogeneity in terms of structural architectures, binding multiplicity, and functional diversity. Many known IDPs are polyampholytesa class of polymers that consists of both positively and negatively charged monomers in varying fractions.…”
Section: Introductionmentioning
confidence: 99%
“…Biomolecular condensates formed via liquid-liquid phase separation of proteins and nucleic acids serve as on-demand membraneless organelles that are involved in the spatiotemporallycontrolled organization, compartmentalization, and regulation inside living cells. Owing to their ability to form and dissipate in response to cellular cues, regulatability, permeability, and the ability to selectively concentrate the biomolecules, these noncanonical liquid-like organelles are emerging as central players at all levels of essential cellular activity ranging from the expression and regulation of genes to the modulation of intricate signaling pathways (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). An emerging body of work has revealed that intrinsically disordered proteins/regions (IDPs/IDRs) often comprising polypeptide repeat units, low sequence complexity, and prionlike domains are ideal candidates for biological phase separation.…”
Section: Introductionmentioning
confidence: 99%